Frequent item set mining using normalized FP-growth algorithm - K. Manikandan, N; Manivannan, D (International Journal of Engineering and Technology, 2018)
As the volume of data and its storage schemes are increasing drastically, the knowledge discovery from these huge volume of heterogeneous and high dimension data emerges as an essential process. Number of algorithms for data association analysis has been introduced considering time and main memory requirements. However this algorithms get completed when the items and records grows extremely high. In this paper we have created a data structure that can be reused without modifying the schema. So the aim of this work is to make an efficient association rule mining independent of the algorithm being selected.Our data structure make data access much faster by simplifying and reorganizing them by implementing shuffling strategy using hamming distance and inverted index mapping. In this work we explore our algorithmâ€™s efficiency by using many datasets containing millions of records in it. We increased the runtime orders of the magnitude and reduced the auxiliary and main memory requirements.Â
Keywords: Item Setmining; FP Growth Algorithm; Association Rule Mining.